Interactions between gold nanoparticles with different morphologies and human serum albumin - Dai, Jiahui; Chen, Chao; Yin, Man; Li, Huixing; Li, Wenbo; Zhang, Zhaowei; Wang, Qian; Du, Zhongyu; Xu, Xiangyu; Wang, Yunfei (Frontiers in Chemistry, 2023)
Introduction: Three different shapes of gold nanoparticles were synthesized in this experiment. At the same time, studies compared their effects with human serum albumin (HSA). Methods: Gold nanoparticles (AuNPs) with three different morphologies, such as, nanospheres (AuNSs), nanorods (AuNRs), and nanoflowers (AuNFs) were synthesized via a seeding method and their characteristic absorption peaks were detected using ultraviolet-visible (UV-vis) absorption spectroscopy, Telectron microscopy (TEM), Dynamic Light Scattering (DLS) and Zeta potential measurements, circular dichroism (CD), and Fourier transform infrared spectroscopy (FTIR) to study the interactions between them and HSA. By comparing the thermodynamic parameters and quenching mechanism of the three materials, similarities and differences were determined in their interactions with HSA. Results: The results showed that with an increase in the concentration of the AuNPs with the three different morphologies, the UV-vis absorption peak intensity of the mixed solution increased, but its fluorescence intensity was quenched. This indicates that the three types of AuNPs interact with HSA, and that the interactions between them represent a static quenching process, which is consistent with the conclusions derived from three-dimensional fluorescence experiments. Through variable-temperature fluorescence experiments, the binding constants, number of binding sites, and thermodynamic parameters of the interactions between the three types of AuNPs and HSA were determined. The Gibbs free energy changes were <0, indicating that the reactions of the three types of AuNPs with HSA are spontaneous, resulting in associated matter. Binding constant measurements indicated that the strongest binding took place between the AuNFs and HSA. In addition, the results of fluorescence, CD spectroscopy, and FTIR showed that three different shapes of AuNPs can induce conformational changes in HSA and reduce the α-helix content. Among them, AuNFs have the smallest ability to induce conformational changes. Discussion: According to studies, AuNFs interact more favorably with HSA. This can be used as a reference for the administration of drugs containing AuNPs.